UPLC/Q-TOF MS Screening and Identification of Antibacterial Compounds in Forsythia suspensa (Thunb.) Vahl Leaves - Zhou, Mingyue; Huo, Jinhai; Wang, Cairen; Wang, Weiming (Frontiers in Pharmacology, 2022)
F. suspensa (Forsythia suspensa (Thunb.) Vahl) is a traditional Chinese medical herb, and only the fruit is used in clinical. However, the other discarded parts, such as leaves, still contain a large number of active components. The research uses the macroporous adsorption resin (MARs) to enrich the effective components of F. suspensa leaves and take advantage of the ultraperformance liquid chromatography coupled with q-tof mass spectrometry (UPLC/Q-TOF MS) to identify it, and next through the high-performance liquid chromatography (HPLC) performed a quantitative analysis. Finally, the antibacterial action of the active components extracted from leaves in vitro was confirmed and the mechanism was explored. Through this experiment, a stable and effective extraction method of antibacterial active components from F. suspensa leaves was obtained and the practicability of leaves was proved, which is beneficial to the more comprehensive utilization of medicinal plant resources.